In-Depth Analysis of Advertising Mistakes - Paramita, Angela Azizah; Maca, Sudirman; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
The study aimed to describe the types of errors in the subject matter as well as describe advertisements that contain elements of greenwashing and hopes to provide a basis for further research in this area. Qualitative descriptive research methods were used to analyze data through psychological approach, including reading, note- taking and analysis techniques. Data collection techniques were carried out using triangulation. The data were analyzed in qualitative descriptive in which the research results emphasized meaning rather than generalization. The object of research in this study was advertising that contains elements of greenwashing of fast fashion brands. The data were analyzed by using semiotic approach. The research results show that the fast fashion brand H&M is involved in greenwashing practices that violate international legal principles such as the precautionary principle and the precautionary principle. It can be seen from excessive claims, hidden information, and the creation of an exaggerated brand image. Their website is not completely accurate, as some fabrics cannot be recycled. The solution used, a mixture of cotton and polyester that makes up 90% of clothing, is difficult to recycle because the fibers are so dense. This program produces chemical waste that needs to be treated.